The Role of Professional Teachers in Strengthening Character Education Through the Pancasila Student Profile at SMAN 1 Gunungsari - Alyana Balqis; Annisa Varelia; Susanti; Auritma Arin Febrianata; Edy Herianto (al-Afkar, Journal For Islamic Studies, 2026)
The research at SMAN 1 Gunungsari explores the implementation of the Merdeka Curriculum through the Pancasila Student Profile Strengthening Project. This school focuses on character development and literacy enhancement, with materials distributed via WhatsApp. The aim of this study is to analyze the professional competencies of teachers at SMAN 1 Gunungsari in implementing the Pancasila Student Profile Strengthening Project and to identify success factors and obstacles in the implementation process, along with solutions for these challenges. This research employs a qualitative method with a descriptive approach, collecting data through interviews and observations for an in-depth analysis of the implementation of the Pancasila Student Profile Strengthening Project (P5). The results indicate two main competencies of teachers emphasized in this project’s implementation, as well as the need to enhance teachers' understanding of student character through the development of these competencies. Support from all parties, including families and schools, is a key factor for the successful implementation of this project. Additionally, varied teaching methods serve as a driving force to achieve success in P5 by producing outcomes that reflect not only products but also changes in students' character and skills at SMAN 1 Gunungsari.